A stabilized single-point finite element formulation for three-dimensional dynamic analysis of saturated soils. (May 2015) - McGann, Christopher R.; Arduino, Pedro; Mackenzie-Helnwein, Peter
Abstract: A low-order single-point quadrature finite element suitable of dynamic 3D analysis of saturated soils is presented. The new element uses a u - p formulation to consider the interaction of the pore fluid and solid skeleton. An hourglass stabilization scheme facilitates single-point integration for the solid phase terms, and non-residual pressure field stabilization is used to facilitate equal-order interpolation for the two phases and improve element behavior in the incompressible–impermeable limit. Several numerical examples are presented to verify the new element formulation and demonstrate its response in a geotechnical application.